Genetic diversity analysis of sapindus in China and extraction of a core germplasm collection using EST-SSR markers - Liu, Jiming (2022)
Sapindus is an important forest tree genus with utilization in biodiesel, biomedicine, and it harbors great potential for biochemical engineering applications. For advanced breeding of Sapindus, it is necessary to evaluate the genetic diversity and construct a rationally designed core germplasm collection. In this study, the genetic diversity and population structure of Sapindus were conducted with 18 expressed sequence tag-simple sequence repeat (EST-SSR) markers in order to establish a core germplasm collection from 161 Sapindus accessions. The population of Sapindus showed high genetic diversity and significant population structure. Interspecific genetic variation was significantly higher than intraspecific variation in the Sapindus mukorossi, Sapindus delavayi, and combined Sapindus rarak plus Sapindus rarak var. velutinus populations. S. mukorossi had abundant genetic variation and showed a specific pattern of geographical variation, whereas S. delavayi, S. rarak, and S. rarak var. velutinus showed less intraspecific variation. A core germplasm collection was created that contained 40% of genetic variation in the initial population, comprising 53 S. mukorossi and nine S. delavayi lineages, as well as single representatives of S. rarak and S. rarak var. velutinus. These results provide a germplasm basis and theoretical rationale for the efficient management, conservation, and utilization of Sapindus, as well as genetic resources for joint genomics research in the future.